Academic self-efficacy, resilience and social support among first-year Israeli nursing students learning in online environments during COVID-19 pandemic. (March 2022) - Warshawski, Sigalit
Abstract: Background: Academic self-efficacy (ASE) has been found to be an important motivator for academic success among nursing students. The associations between ASE, resilience and social support have not been fully explored among nursing students, especially those in their first year who are learning online. Objectives: To explore a) the associations between ASE, resilience and social support among first-year nursing students learning in an online learning environment; and b) students' views regarding the difficulties they have encountered and the available assistance. Design and methods: A cross-sectional survey design on a sample of 222 undergraduate first-year Israeli nursing students. Questions were uploaded in the format of a commercial internet survey provider (Qualtrics.com ) and distributed through the university's online learning platform. Results: Positive correlations were found between ASE and resilience and social support. Significant differences were found in the research variables according to the students' gender, cultural group and their perceived difficulty in studies. Resilience, social support, perceived difficulty in studies and being a female explained 31% of the students' variance in ASE. Conclusions: Nurse educators should develop and promote strategies to enhance students' resilience and perceived social support. These have the potential to significantly improve students' ASE also in online environments. In addition, faculty should promote the preparation of online learning environments in accordance with students' needs and proficiencies. Highlights: ASE was found positively associated to resilience and social support. ASE is negatively associated to students' perceived difficulty in studies Resilience, social support and perceived difficulty in studies explained ASE Resilience and social support could improve students' ASE in online environments